Responsible Conduct of Research Measure: The initial development and pilot study - Willse, John T; Wester, Kelly L. (2008)
Although much discussion has been focused on research misconduct (RM) and questionable research practices, to date no self-report measures exist to examine this phenomenon. To help fill this void, the authors developed the Responsible Conduct of Research Measure (RCRM) through multiple pilot study waves involving researchers in the social and behavioral sciences. Preliminary results reveal adequate validity and reliability. The authors discuss limitations of the study as well as some possible directions for future research on this topic